2010
DOI: 10.1002/clc.20851
|View full text |Cite
|
Sign up to set email alerts
|

Confidential Testing of Cardiac Examination Competency in Cardiology and Noncardiology Faculty and Trainees: A Multicenter Study

Abstract: Background: Many reported studies of medical trainees and physicians have demonstrated major deficiencies in correctly identifying heart sounds and murmurs, but cardiologists had not been tested. We previously confirmed these deficiencies using a 50-question multimedia cardiac examination (CE) test featuring video vignettes of patients with auscultatory and visible manifestations of cardiovascular pathology (virtual cardiac patients). Previous testing of 62 internal medical faculty yielded scores no better tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
24
0
2

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 35 publications
(27 citation statements)
references
References 16 publications
1
24
0
2
Order By: Relevance
“…For example, cardiac examination skills have been shown to improve during the early years of medical school and then plateau by the third year, with no measurable improvement through residency or beyond without fellowship training. [1][2][3] Despite efforts by residency programs to promote bedside teaching, many general medicine faculty shy away due to lack of confidence and comfort in teaching physical diagnosis. 4 The presence of hospitalists increases satisfaction among trainees with inpatient teaching, 5 and medical faculty's ability has been shown to positively impact medical students' test scores.…”
Section: Resultsmentioning
confidence: 99%
“…For example, cardiac examination skills have been shown to improve during the early years of medical school and then plateau by the third year, with no measurable improvement through residency or beyond without fellowship training. [1][2][3] Despite efforts by residency programs to promote bedside teaching, many general medicine faculty shy away due to lack of confidence and comfort in teaching physical diagnosis. 4 The presence of hospitalists increases satisfaction among trainees with inpatient teaching, 5 and medical faculty's ability has been shown to positively impact medical students' test scores.…”
Section: Resultsmentioning
confidence: 99%
“…In general, performance on the assessment peaks during the third year of medical school, compared to other medical school years, internal medicine residency and general practice. Only cardiology fellows and cardiology faculty outperform other groups on the assessment [20][21][22]. Incoming interns from 2015-2016 and 2016-2017 took the CE two weeks prior to the start of intern year and at the midpoint of the year.…”
Section: Cardiovascular Skills Assessmentmentioning
confidence: 99%
“…It is not surprising that less time at the bedside has contributed to a measurable decline in physical exam skills [13][14][15][16][17], in part due to a decreased emphasis on physical diagnosis teaching and practice [7,15,18,19]. Alarmingly, some studies have shown that physical exam skills, particularly cardiovascular exams skills, peak during medical school and decline during residency and beyond [20][21][22]. Physical exam findings directly and immediately affect patient outcomes; a decline in exam skills could have adverse effects on patient care [23,24].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Despite decades of pleas to reprioritize PE, 9 GME training in aspects of PE is underemphasized whenever formally assessed. [10][11][12][13][14] Furthermore, residents' examination skills in many contexts, including cardiovascular, pulmonary, breast, rheumatologic, and genitourinary systems, among others, [15][16][17][18][19][20][21][22][23][24][25][26][27][28][29][30][31][32][33][34] are suboptimal.…”
Section: Introductionmentioning
confidence: 99%